A wearable soft-robotic glove enables hand support in ADL and rehabilitation: A feasibility study on the assistive functionality. (November 2016) - Radder, Bob; Prange-Lasonder, Gerdienke B; Kottink, Anke IR; Gaasbeek, Liesbeth; Holmberg, Johnny; Meyer, Thomas; Melendez-Calderon, Alejandro; Ingvast, Johan; Buurke, Jaap H; Rietman, Johan S
Background: Elderly people frequently experience a decline in hand function, due to ageing or diseases. This leads to decreased independence in activities of daily living (ADL). Assistive technology may enhance independence. Objectives: The objective of this paper was to explore user acceptance of an affordable wearable soft-robotic glove (ironHand (iH) system), that supports grip and hand opening in ADL. In addition, functional performance with the iH system was explored. Methods: For this study 28 elderly people used the iH system across two sessions. During these sessions, participants performed six functional tasks with and without the iH system. Outcome measures were System Usability Scale (SUS), Intrinsic Motivation Inventory (IMI) and performance time of the functional tasks. Results: User acceptance scored highly, with a mean SUS score of at least 63.4 (SD = 19.0) and a mean IMI score of 5.1 points (SD = 0.97 points). Functional task performance improved across repetitions both with and without the glove ( p ≤ 0.017), but all functional tasks were performed faster without the glove ( p ≤ 0.032). Conclusion: Participants perceived the iH system as useful, pleasant and meaningful. The learning curve in functional performance time (improvements across repetitions) is promising, since it suggests there is room for improved performance when a longer acquaintance period is applied.